It takes two to Tango: Two gates orchestrate the opening of human TRPM2. (January 2022) - Rish, Anthony D.; Shen, Zhangfei; Fu, Tian-Min
Highlights: The selectivity filter of human TRPM2 has dual functions: ion selectivity and gating. The opening of human TRPM2 is orchestrated by two gates. TRPM2 across evolved divergent gating mechanisms. Abstract: TRPM2 is a calcium permeable non-selective cation channel involved in many important physiological processes and has divergent gating mechanisms across species. Structural studies have revealed that TRPM2 is gated by adenosine 5′-diphosphoribose that binds to the cytosolic domains of TRPM2 and calcium ions that are coordinated by residues in the transmembrane domain. However, the selectivity filter of human TRPM2 remains elusive due to the poor resolution in this region. In a recent manuscript published in Cell Reports, Yu et al. present unexpected dual roles of the selectivity filter in human TRPM2 by determining a high-resolution structure of human TRPM2 in lipid nanodiscs. This study provides unprecedented insights into the gating mechanism of human TRPM2. Graphical abstract: Image, graphical abstract